Reflection of teachers’ pedagogical competence in Daik Lingga Regency: An analysis - Rosadi, Khairi; Irawan, Dody; Kurmalasari, Tety; Nevrita , Nevrita; Hajar, Encik Abdul (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study analyzes the pedagogical competence profile of teachers in Daik Lingga Regency, an archipelago region in Indonesia, to inform contextual professional development. Using a sequential explanatory mixed-method design, it first quantitatively analyzed Training Needs Assessment (TNA) data from 804 educators against the national Teacher Competency Model (2023). Results indicate that overall pedagogical competence ranges from Level 3 (Evaluating) to Level 4 (Proficient). However, a critical disparity was found: competence in “Adaptive use of ICT” (sub-indicator 1.2.5) scored lowest (mean 2.980, Level 3), identifying it as a top training priority. In contrast, “Creating a safe and comfortable learning environment” (sub-indicator 1.1.3) scored highest (mean 3.420, Level 4). The low ICT score empirically validates contextual challenges related to infrastructure and connectivity in this island region. This quantitative finding triggers the subsequent qualitative phase to explore the underlying hindering factors. The study concludes that data-driven policy is crucial, recommending targeted professional development focused on adaptive digital skills to address the specific gaps and improve educational quality in Indonesia’s outermost regions.